A Cross-Generational Da’wah Strategy for Fostering an Understanding of Islam Among Generation Y and Generation Z in Aceh - Jasafat Jasafat; Syahril Furqany; Syamira Balqis; Syukri Syamaun; Ridwan Muhammad Hasan (Kalijaga Journal of Communication, 2026)
The transformation of da'wah media has become a central issue in the dynamics of religious life across generations in Aceh, especially between Generation Y (millennials) and Generation Z, which has not been seen in da'wah. The striking differences in the patterns of understanding and practising Islam between the two generations indicate communication challenges and the need for da'wah strategies to bridge these differences effectively. Generation Y tends to access Islamic teachings through traditional channels such as dayah and study religion, and adheres to the authority of local ulama. Meanwhile, Generation Z forms an understanding of Islam through social media, digital da'wah, and "relatable" religious figures, with a more contextual and personal approach. In Aceh, the shift in Gen Z's religious orientation is active in digital da'wah content and online Islamic discussions, while Gen Y is more dominant in conventional religious forums. However, this gap can cause polarization, even tension, if not facilitated by an inclusive and adaptive da'wah approach to the character of each generation. Using descriptive qualitative methods and a field study approach in urban and semi-urban areas in Aceh, this study focuses on analyzing the effectiveness of da'wah media in uniting religious visions across generations. The study results found that the da'wah press, which combines traditional values with interactive digital formats, has greater reach and acceptance across generations. This study's novelty lies in submitting a collaborative da'wah model across generations that does not position generations as competitors but as partners in the ongoing process of interpreting Islam. This study is critical-constructive, emphasizing the importance of da'wah as a space for dialogue, not domination, to maintain socio-religious harmony amidst changing times.